Optimización del proceso de elaboración de pan utilizando harina de maíz morado (Zea mays L) - Hernandez Tejada, Mercy Milagros (2017)
The objective of this work was to develop a biscuit with purple corn flour (Zea mays l) of high acceptability. The bread was made by replacing a portion of wheat flour with purple corn flour according to the traditional method. A rotational central composite design 22 including 4 axial and 3 central were used, wich allowed obtaining models that define the behavior of the independet variables percentage purple corn flour substitution (2% to 8%) and baking temperatura (100 ºC to 170 ºC) thant it was dependent overall acceptability. The only model with a highly significant (p < 0.05) was for the baking temperatura by having a high coefficient of determination R2, making it posible to build the response surfaces for this STATISTICA 7.0 software was used. General acceptability of optimal biscuit (score of 7.4) was obtained when substituted between 2% and 4% purple corn flour and a temperatura between 130 ºC and 140 ºC bake a time of 15 minutes.